PS-C28-9: AMBULATORY BP DERIVED SALT SENSITIVITY INDEX AS A PREDICTOR OF THE BP RESPONSE TO RENAL DENERVATION. (January 2023) - Ashton, Jonathon Sesa; Carnagarin, Revathy; Nolde, Janis M; Schlaich, Markus
Abstract : Objective: Renal denervation (RDN) has been consistently shown in recent sham-controlled clinical trials to reduce clinic and ambulatory blood pressure (BP). Salt sensitivity is a critical factor in hypertension pathogenesis and severity, but cumbersome to assess by gold-standard methodology. 24-hour average heart rate and mean arterial pressure dipping, taken by ambulatory blood pressure monitoring (ABPM), can stratify patients into high, moderate and low salt sensitivity index (SSI) risk categories. Here we aimed to assess whether ABPM-derived SSI risk could predict the systolic blood pressure reduction at long-term follow-up in a real-world cohort of RDN patients. Design and Methods: 60 participants (70.0 ± 10.3 years, 76.3% male) had repeat ABPM assessment as part of a renal denervation long-term follow and compared to their pre-RDN baseline for calculating systolic BP changes. Average time since RDN was 8.7 years ± 1.09 years. Participants were stratified into low, moderate and high SSI Risk groups, respectively. MAP dipping less than 10% and heart rate (HR) greater than 70 indicated high-risk, MAP dipping greater than 10% and HR less than 70 indicated low risk. Remaining participants were classified as moderate risk. Systolic BP changes in risk groups were compared by One-way ANOVA. Multiple regression was computed for systolic BP response, baseline SBP and High SSI Risk status. Results: One-way ANOVA indicated a significant treatment effect (p = 0.03) between low, moderate and high salt-sensitivity index risk calculated by ABPM measures with systolic BP reduction of 9.64 ± 3.74 mmHg, 8.41 ± 3.48 mmHg, and 28.20 ± 9.55 mmHg, respectively. Baseline SBP was not significantly different between SSI Risk groups (p = 0.18), but trended upward with increasing SSI. High SSI risk independently correlated with systolic BP reduction (p = 0.02). Conclusions: Our preliminary investigation indicates that SSI risk may serve as a simple and easily accessible measure for prediction of the BP response to RDN. However, the influence of pharmacological therapy on these participants is an important extraneous variable requiring testing in prospective or drug-naive RDN cohorts.